(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The aim of the research is to experimentally test and scientifically substantiate the mixture of lake clay and a natural active agent – essential oil, in perspective of its application in cosmetology and dermatology. Sensory properties of lake clay and mixtures of lake clay with essential oils were tested. The presence and quantity of Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, Escherichia coli, and aerobic mesophilic microorganisms in lake clay and lake clay with essential oils mixtures were determined. Thyme (Thymus vulgaris), apple mint (Mentha suaveolans), and caraway (Carum carvi) essential oils, which not only improve the cosmetic value of the product but also act as antimicrobial agents and preservatives, showed the best results. They meet the requirements of Latvian Cabinet Regulation No. 354 “Procedure for Meeting the Significant Requirements for Cosmetics” and European Standard EN ISO 17516: 2014, Cosmetics - Microbiology - Microbiological limits.